2021
DOI: 10.1007/s12571-021-01202-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of complementary feeding in India’s high child malnutrition rates: findings from a comprehensive analysis of NFHS IV (2015–2016) data

Abstract: Relative to its economic growth and poverty levels, Indian children suffer from higher levels of malnutrition than children in many other low- and middle-income countries. Research presented in this article examined the links between infant and young child feeding practices among Indian children and their rates of stunting, underweight, wasting, and anaemia, with a particular focus on the types of semisolid complementary food consumed. It did so through a comprehensive analysis of data on more than 57,000 6-to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…With developed states such as Kerala, Goa and Karnataka reporting an increase in MDDF between 2005–6 and 2015–16, as well as large clusters of districts with high MDDF covering highly populated states in India, poor IYCF practices among children in India seem widespread. Recent studies ( 25 , 26 ) also identified that strengthening IYCF programmes would require intensive focused intervention to control MDDF in select districts, especially aspirational districts in high-focus group states in India. The present study presents the association of MDDF with a range of factors, including child, maternal, household and regional characteristics of children, their healthcare exposure and concurrent health status.…”
Section: Discussionmentioning
confidence: 99%
“…With developed states such as Kerala, Goa and Karnataka reporting an increase in MDDF between 2005–6 and 2015–16, as well as large clusters of districts with high MDDF covering highly populated states in India, poor IYCF practices among children in India seem widespread. Recent studies ( 25 , 26 ) also identified that strengthening IYCF programmes would require intensive focused intervention to control MDDF in select districts, especially aspirational districts in high-focus group states in India. The present study presents the association of MDDF with a range of factors, including child, maternal, household and regional characteristics of children, their healthcare exposure and concurrent health status.…”
Section: Discussionmentioning
confidence: 99%
“…According to the ICDS program, only 20% of children in the pre-primary stage regularly obtain SNP benefits [20]. Children who 'fully' participated in the ICDS (received food rations, medical checkups, and weigh-ins, and attended preschool) and received daily food rations from the program showed a significant decline in malnutrition status [21]. In states and districts where undernutrition is more common, the ICDS program must focus on younger children (0-3 years) and the most vulnerable population segments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed nutritional outcomes of participants of the scheme. Three studies suggest that nutritional outcomes have not improved among beneficiaries, 9 11 while another study suggests that service utilization is linked to improved weight for age. 12 One nationally representative study noted that beneficiaries had more diverse diets relative to a control group.…”
Section: Introductionmentioning
confidence: 99%
“…12 One nationally representative study noted that beneficiaries had more diverse diets relative to a control group. 11 From an implementation perspective, to discern why activities might not lead to improved nutrition, it is essential to understand the intermediary steps involving nutritional knowledge and practices. We therefore aimed to estimate the association of all major nutritional activities delivered through the scheme (under the enhanced POSHAN Abhiyaan approach) to pregnant and lactating mothers and their children with nutrition knowledge and practices among the beneficiaries.…”
Section: Introductionmentioning
confidence: 99%